ADHD Comorbid With Major Depression on Parents and Teachers Perceptions. Issue 4 (February 2021) - Coutinho, Daniele; Farias, Antonio Carlos; Felden, Erico Pereira Gomes; Cordeiro, Mara L
Objective: Examine the Strengths and Difficulties Questionnaire (SDQ) responses of parents and teachers for children with ADHD comorbid with major depressive disorder (MDD), with an emphasis on determining how well the respondent groups' responses correlate, and how well the results obtained perform as predictors of clinical diagnosis.Method: The SDQ was completed by parents and teachers of ( n = 215 participants, 7-12 years old) in ADHD, MDD, ADHD + MDD, and healthy control groups. Agreement between parent and teacher SDQs and their concordance with Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV ) diagnoses were assessed. Receiver operating characteristic (ROC) and Kappa concordance analyses were used to compare the groups with the health control group.Results: The comorbid group presented greater impairments than the ADHD, MDD, and control groups ( p < .001).Conclusion: The presence of psychiatric comorbidity causes greater impairment for school children with ADHD. The SDQ has good sensitivity for detecting these children and correlates well with DSM diagnosis.